Building a Resilient and Sustainable Agriculture in Sub-Saharan Africa (Springer International Publishing, 2018)
This book is open access under a CC BY 4.0 license What are the challenges and action points for agricultural sustainability in Sub-Saharan Africa? This collection of papers offers technical analyses, policy recommendations and an overview of success stories to date. Each carefully selected paper provides valuable insights for improved policy making and defines relevant strategic priorities on Africa's sustainable transformation process, which is in line with the international development agenda. Although agriculture remains the main source of income for Africa's population, the sector is rain-fed subjecting it to the vagaries of weather and climate change. This volume demonstrates the rationale of developing a competitive, inclusive and sustainable agribusiness sector for Africa's food security and structural transformation. From the impact of Bioenergy crop adoption and Drought Index Insurance to Agro-Industrialization, this volume is important reading for individual researchers, academic associations and professional bodies interested in African agricultural development.